Design Optimisation of Outer Hood Panel of Esemka R2 Car to Improve Pedestrian Protection - Binyamin, B; Riyadi, Tri Widodo Besar (Universitas Muhammadiyah Surakarta, 2024)
Traffic accidents are terrible scourge that occur in many countries, specially for developing countries where transportation affairs like tangled yarn. Besides functioning as an engine compartment cover, the hood of modern compact SUV can also help to manage the impact energy of a pedestrian's head in a vehicle-pedestrian impact. This paper presents outer hood design of Esemka R2 that has a potential to improve hood's ability and also to absorb the impact energy of a pedestrian's head. The developed method for the design of an outer hood configuration aims to provide a robust design and homogeneous of Head Injury Criterion (HIC) for impact position at WAD 1000 and three different thicknesses (1.25 mm, 1.35 mm & 1.50 mm) of outer hood panel of Esemka R2 compact SUV, taking into consideration the limited space available for deformation. The non-linear Finite Element Analysis (FEA) software (Explicit Dynamics) was used in this research to simulate the testing procedurs of head impact for child pedestrian. The results show that the average of comparison dimensional of outer hood panel of Esemka R2 was 4.89 mm. The minimum of deformation space meet the requirement for HIC value which required obtaining robust and homogeneous head impact performance. Outer hood thickness and materials were identified as the factors to influence the stress and HIC value of the hood. By comparing all outer hood panels, aluminium alloy as the best selected material which has the lowest value is 32.78% for the pedestrian protection.